IMPLEMENTASI METODE NAIVE BAYES UNTUK KLASIFIKASI PENENTUAN KELAS PENGAJIAN DI MA’HAD AL-JAMI’AH UNHASY TEBUIRENG JOMBANG - Khoiry Mahmud; Ahmad Heru Mujianto; Mufarrihah, Iftitaahul; Muhammad Fatkhur Rizal (Fakultas Teknologi Informasi, 2024)
Data mining is a phase in the knowledge discovery in databases (KDD) process that seeks to identifyimportant, useful, and simply understandable new patterns or models. The recitation class at Ma'had Al-Jami'ah UNHASY Tebuireng Jombang was established using the classification method in data mining forthis study. Ma'had Al-Jami'ah UNHASY is an educational institution associated with Hasyim Asy'ariUniversity. Its primary focus is on fostering entrepreneurship and pesantren. Currently, the selectionprocess for recitation classes, specifically tahfidz and tahsin classes, is still carried out manually, leading toa time-consuming and ineffective procedure. The aim of this project is to develop a classification systemthat utilizes the Naïve Bayes method to accurately identify recitation classes. The Naïve Bayes approachwas chosen for its simplicity and ease of implementation. The dataset attributes used in this inquiry are thetest results of the mahasantri in writing, memory, and reading the Quran. This research is expected to helpthe administration of Ma'had Al-Jami'ah UNHASY in improving the process of selecting recitation classesto make it more efficient and effective. Furthermore, it will provide a system with the ability to categorizethe classes of Ma'had Al-Jami'ah mahasantri into two distinct groups: